2004
DOI: 10.1111/j.1463-5224.2004.04022.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the photopic ERG i‐wave in different species

Abstract: The i-wave, a post b-wave component of the human photopic electroretinogram (ERG), is claimed to originate at the level of the retinal ganglion cells (RGC) or more distally. We investigated whether this wave is a feature common to all species. Photopic ERGs were obtained from the following species: Beagle dog, European cat, New Zealand white rabbit, Göttingen minipig, Cynomolgus monkey, Sprague-Dawley and brown Norway rats, Hartley guinea pig, and CD1 and C57BL6 mice. Results were compared with those obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 7 publications
7
24
0
3
Order By: Relevance
“…Kommonen et al [8] demonstrated that dogs anesthetized with a fast injection of propofol had an obvious increase in the amplitude of the bwaves. In recent years, ketamine, xylazine, and medetomidine have been used as anesthetic agents for conducting ERG examinations [4,12].…”
mentioning
confidence: 99%
“…Kommonen et al [8] demonstrated that dogs anesthetized with a fast injection of propofol had an obvious increase in the amplitude of the bwaves. In recent years, ketamine, xylazine, and medetomidine have been used as anesthetic agents for conducting ERG examinations [4,12].…”
mentioning
confidence: 99%
“…In the earlier studies [10,11,12,13], the PhNR analysis was made in the recordings of photopic ERG that was elicited by a short stimulus (<6 ms), and the amplitude of the PhNR might be affected by the i-wave [16,17,18]. The photopic ERG using long-duration (150 ms) stimuli can minimize the influence of the i-wave, which is thought to be associated with the off component [10, 18, 19] of the photopic ERG.…”
Section: Introductionmentioning
confidence: 99%
“…ERG exams have been performed in the latest years with the use of xylazine, ketamine and medetomidine as anesthetic agents (Chaudieu 2004, Rosolen et al 2004). The combination of xylazine and butorphanol in this study, provided a good sedation and allowed adequate recording and low noise interference.…”
Section: Discussionmentioning
confidence: 99%